STOCK-EXCHANGE MARGINS. - Smith, F. P. (The Accounting Review, 1934)
One of the most bitterly contested provisions of the Securities Exchange Act of 1934 was the provision relating to marginal transactions and maximum loanable values of securities. Two different provisions were incorporated in the bills of the House and Senate, the resulting act being a modification of the House bill. Marginal transactions have long been the subject of reform movements. The Hughes Committee of 1909 was requested, specifically, to inquire into margin trading. A Federal judge furnished the Senate Committee with instances from his long experience on the bench, indicating that a large proportion of business failures, embezzlements and even suicides in recent years were directly attributable to losses incurred in speculative transactions. Measures were suggested during the last session of the U.S. Congress to abolish margin trading and the Senate Committee deemed the radical step unwise only because of the deflationary consequences which might follow. Marginal transactions involve the buying and selling of securities with the aid of borrowed money. The amount of money which the purchaser or seller must advance has in the past been a matter of agreement between the customer and the brokerage house. Funds advanced by the customer represented an advance for the protection of the brokerage house, not for the protection of the customer.